Formulation of nano-graphene doped with nano silver modified dentin bonding agents with enhanced interfacial stability and antibiofilm properties. Issue 2 (February 2022) - Akram, Zohaib; Aati, Sultan; Clode, Peta; Saunders, Martin; Ngo, Hien; Fawzy, Amr S.
Highlights: GNP/nAg created well-defined hybrid layer and regularly formed long resin tags. Addition of 0.25% GNP/nAg showed optimized anti-biofilm and mechanical properties. Addition of GNP/nAg did not affect the standard adhesion characteristics. Graphical Abstract: ga1 Abstract: Objective: The aim of this study was to synthesize and characterize reduced nano graphene oxide (RGO) and graphene nanoplatelets (GNPs) doped with silver nanoparticles (nAg) and to prepare an experimental dentin adhesive modified with RGO/nAg and GNP/nAg nanofillers for studying various biological and mechanical properties after bonding to tooth dentin. Methods: Nanoparticles were characterized for their morphology and chemical structure using electron microscopy and infrared spectroscopy. Experimental dentin adhesive was modified using two weight percentage (0.25% and 0.5%) of RGO/nAg and GNP/nAg to study its degree of conversion (DC), antimicrobial potential, and cytotoxicity. The effect and significance of these modified bonding agents on resin-dentin bonded interface were investigated by evaluating interfacial nanoleakage, micropermeability, nanodynamic mechanical analysis, micro-tensile bond strength (µTBS), and four-point bending strength (BS), Results: Both 0.25% and 0.5% GNP/nAg graphene-modified adhesives showed comparable DC values to the commercial and experimental adhesive (range: 42–46%). The bacterial viability of the groups 0.25% and 0.5% GNP-Ag remained very low under 25% compared to RGO/nAg groups with low cytotoxicity profiles (cell viability>85%). Resin-bonded dentin interface created with GNP/nAg showed homogenous, well-defined hybrid layer and regularly formed long resin tags devoid of any microporosity as evidenced by SEM and confocal microscopy. The lowest nanoleakage and highest bending strength and µTBS was recorded for 0.25% GNP/nAg after 12 months of ageing. A significantly increased nanoelasticity was seen for all experimental groups except for control groups. Significance: The addition of 0.25% GNP/nAg showed optimized anti-biofilm properties without affecting the standard adhesion characteristics.